The Last Remaining Jesuit in China after Suppression in Europe - LIU, Jingjing (International Journal of Sino-Western Studies, 2022)
This paper will attempt to show the Jesuits’ situation in China and Russia through Fr Louis de Poirot (1735–1813 賀清泰)’s life. He was the last remaining Jesuit in China (the new Jesuits returned to mainland China on 11 June 1842), and was a link between the Old Jesuits and New Jesuits.The first section will introduce his life in the Chinese court. He was the last of the Western painters who worked for Qianlong along with Father Giuseppe Panzi. The two painters replaced the more famous fathers Giuseppe Castiglione and Jean-Denis Attiret. He was also in charge of the translation between Latin and Manchu for the diplomatic correspondence between Pekin and Saint Petersburg. He was the first to translate most of the Bible into Chinese and Manchu. The paper will show the attitude of Chinese Emperor and other official’s attitude to the suppression, Did they even care about the suppression of the Jesuits? What’s of any concern to them? The second section will present a precious letter received from Father General Brzozowski written on Sept. 25, 1806 with the help of the Russian ecclesiastical mission. Father General Brzozowski asked whether Fr Louis de Poirot had received Gruber’s permission to rejoin the Society and to enquire about the situation of the other fathers in China and the Chinese church. He also mentioned their attemption to enter China and the Jesuits’ situation all over the world.